Use of a Web‐based Education Program Improves Nurses' Knowledge of Breastfeeding. Issue 1 (7th January 2015) - Deloian, Barbara J.; Lewin, Linda Orkin; O'Connor, Mary E.
ABSTRACT: Objective: To evaluate the baseline knowledge and knowledge gained of nurses, nursing students, midwives, and nurse practitioners who completed Breastfeeding Basics, an online educational program. Design: This study reports on an anonymous evaluation of an online breastfeeding education program developed and maintained to promote evidence‐based breastfeeding practice. Participants: Included in the study were 3736 nurses, 728 nurse practitioners/midwives, and 3106 nursing students from the United States who completed ≥ one pretest or posttest on the Breastfeeding Basics website between April 1999 and December 31, 2011. Methods: Baseline scores were analyzed to determine if nurses' baseline knowledge varied by selected demographic variables such as age, gender, professional level, personal or partner breastfeeding experience, and whether they were required to complete the website for a job or school requirement and to determine knowledge gaps. Pretest and posttest scores on all modules and in specific questions with low pretest scores were compared as a measure of knowledge gained. Results: Lower median pretest scores were found in student nurses (71%), males (71%), those required to take the course (75%), and those without personal breastfeeding experience (72%). The modules with the lowest median pretest scores were Anatomy/Physiology (67%), Growth and Development of the Breastfed Infant (67%), the Breastfeeding Couple (73%), and the Term Infant with Problems (60%). Posttest scores in all modules increased significantly ( p  < .001). Conclusion: Breastfeeding Basics was used by a large number of nurses and nursing students. Gaps exist in nurses' breastfeeding knowledge. Knowledge improved in all areas based on comparison of pretest and posttest scores.